2019
DOI: 10.18821/0016-9900-2016-95-6-588-592
|View full text |Cite
|
Sign up to set email alerts
|

Research of the inactivation of pathogens in water under exposure to low temperature plasma

Abstract: There was investigated the effect of barrier and spark discharge low temperature plasma on water containing the cells of Escherichia coli (Escherichia coli), hay bacillus (Bacillus subtilis) and yeast (Saccharomyces cerevisiae). There was shown a general decline in the concentration of viable microbial cells after the treatment of suspensions. There was especially marked the detrimental effect of the method on the viability of sanitary-indicative coliform bacteria in the water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…However, it reduces the infection with phytopathogenic fungi [3]. In addition, domestic studies [1,4,5] demonstrated the bactericidal effect of NTAP on several microorganisms: yeast, gramnegative, and gram-positive bacteria, and their spore forms. It is also worth noting the formation of free radicals due to plasma chemical reactions, which are strong oxidants [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, it reduces the infection with phytopathogenic fungi [3]. In addition, domestic studies [1,4,5] demonstrated the bactericidal effect of NTAP on several microorganisms: yeast, gramnegative, and gram-positive bacteria, and their spore forms. It is also worth noting the formation of free radicals due to plasma chemical reactions, which are strong oxidants [6,7].…”
Section: Introductionmentioning
confidence: 99%